IgG4-related sialadenitis complicated with type III mixed cryoglobulinemia: A case report. Issue 31 (August 2019) - Zhang, Rui-Yu; Zhao, Zhi-Rui; Xu, Xiao-Yi; Sun, Li-Jun; Dong, Hong-Rui; Rui, Hong-Liang; Wang, Guo-Qin; Cheng, Hong; Chen, Yi-Pu
Abstract: Rationale: IgG4-related disease (IgG4-RD) is a systemic autoimmune disease and mixed cryoglobulinemia may be caused by autoimmune diseases. However, so far only 1 case of IgG4-RD complicated with mixed cryoglobulinemia is reported. Our case further confirms the close relationship between these 2 diseases. Patient concerns: A 55-year-old female was admitted because of dry mouth and teeth falling off. Diagnoses: The patient was diagnosed as IgG4-related sialadenitis (IgG4-RS) complicated with type III mixed cryoglobulinemia. IgG4-RS was confirmed by elevated serum IgG4 levels and diffuse IgG4 + plasmocyte infiltration and storiform fibrosis in the interstitium of labial gland. Type III mixed cryoglobulinemia was confirmed by positive serum cryoglobulins and no monoclonal immunoglobulin in serum and urine. Interventions and Outcomes: After treatment with prednisone and cyclophosphamide, serum cryoglobulins rapidly turned negative with the remission of IgG4-RS. Lessons: Type III mixed cryoglobulinemia can be caused by IgG4-RS, and the underlying mechanisms need to be further explored.